2010
DOI: 10.1038/jcbfm.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

α-MSH: A Potential Neuroprotective and Immunomodulatory Agent for the Treatment of Stroke

Abstract: Alpha-melanocyte-stimulating hormone (MSH) is a neuropeptide with profound immunomodulatory properties; we evaluated the effects of a-MSH on stroke outcome and its ability to modulate the postischemic immune response. In Lewis rats subjected to 3 hours of middle cerebral artery occlusion (MCAO), plasma concentrations of a-MSH rapidly decreased and returned to baseline over the course of days. Exogenous administration of a-MSH (100 or 500 lg/kg) improved 24 hour outcome in animals subjected to 2 hours MCAO; a-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…28,29 We also found that α -MSH administration decreased infarct volume and improved neurological outcome 24 hours after transient middle cerebral artery occlusion in an animal model of stroke. 7 Consistent with the known effects of α -MSH on the immune response, we found that splenocytes harvested from α -MSH–treated animals responded less well to phytohemagglutinin (a lymphocyte mitogen) than splenocytes harvested from saline-treated animals. Furthermore, the animals treated with α -MSH in this study were less likely to develop autoimmune responses to myelin basic protein, a response associated with worse stroke outcome.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…28,29 We also found that α -MSH administration decreased infarct volume and improved neurological outcome 24 hours after transient middle cerebral artery occlusion in an animal model of stroke. 7 Consistent with the known effects of α -MSH on the immune response, we found that splenocytes harvested from α -MSH–treated animals responded less well to phytohemagglutinin (a lymphocyte mitogen) than splenocytes harvested from saline-treated animals. Furthermore, the animals treated with α -MSH in this study were less likely to develop autoimmune responses to myelin basic protein, a response associated with worse stroke outcome.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, this is the first study that addresses endogenous changes in plasma α -MSH after ischemic stroke, although we did find a similar decrease in plasma α -MSH in an animal study of severe stroke. 7 Further, we found that higher plasma α -MSH was associated with an increased likelihood of experiencing a good clinical outcome, an effect that was most apparent at later time points after stroke and independent of stroke severity, patient age, and infection status. In contrast, the associations between cortisol and IL-6 on outcome were most robust at early time points after stroke and explained almost entirely by the fact that cortisol and IL-6 are markers of stroke severity.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…All of the finely integrated key components and upstream regulators of the melanocortin system have widespread immunologic influence modulated via their downstream targets [Xiao et al, 2003;La Cava and Matarese, 2004;Matarese and La Cava, 2004;Taub, 2008;Savos et al, 2011] and some also act as neuroimmune cotransmitters [Bedoui et al, 2003]. Cytokines are the effector molecule links between immune response and the neuroendocrine system.…”
mentioning
confidence: 99%